THEORIES OF CORPORATE INSOLVENCY: A PHILOSOPHICAL ANALYSIS OF THE CORPORATE RESCUE MECHANISMS UNDER THE COMPANIES ACT 2016 (UUM Journal of Legal Studies, 2021)
This paper aims to provide an examination of the theories that underpin corporate insolvency as developed in the US and the UK, and apply that to the two novel corporate rescue mechanisms; the corporate voluntary arrangement and judicial management, which are embedded in the Companies Act 2016 (CA 2016) of Malaysia. This paper adopted a doctrinal and theoretical approach to law. The tension in the corporate rescue mechanisms in the CA 2016 between creditors and other stakeholders of a company affected the objectives on corporate insolvency in Malaysia. This paper identified the theories that are reflected in the corporate rescue mechanisms in the CA 2016– a gap within the provisions which was left out in the process that ranged from consultancy and leading up to the drafting of the CA 2016. In addition, the objectives of introducing the corporate rescue mechanisms were identified. These findings may pave the way to reform the corporate rescue law in order to enhance its conformity with the objectives of corporate rescue in Malaysia. This in turn would facilitate the recovery of financially distressed companies and the minimisation of the loss of employment.